A new species and new record of the leafhopper genus Balclutha (Hemiptera: Cicadellidae: Deltocephalinae) from China with key to species - Sun, Jing; Zhang, Yalin; Lu, Lin; Webb, M. D. (Zootaxa, 2019)
A new species, Balclutha longispina sp. nov. from Yunnan Province of China, is described and Balclutha sinuata Webb & Vilbaste is recored from China (Tibet) for the first time. A key to males of Chinese Balclutha species is provided.